Hindu-Catholic encounters in Goa: religion, colonialism, and modernity - Henn, Alexander (Indiana Univ. Press, 2014)
"The state of Goa on India's southwest coast was once the capital of the Portuguese-Catholic empire in Asia. When Vasco Da Gama arrived in India in 1498, he mistook Hindus for Christians, but Jesuit missionaries soon declared war on the alleged idolatry of the Hindus. Today, Hindus and Catholics assert their own religious identities, but Hindu village gods and Catholic patron saints attract worship from members of both religious communities. Through fresh readings of early Portuguese sources and long-term ethnographic fieldwork, this study traces the history of Hindu-Catholic syncretism in Goa and considers its implications for our understanding of power, religion, and postcoloniality"--
Includes bibliographical references (pages 191-204) and index
Keywords: Catholic Church -- Relations -- Hinduism; Goa (India : State) -- Religious life and customs; Goa (India : State) -- Religion; Synkretismus; Hinduismus; Christentum; Goa